Readiness of Teaching Staff to Ensure Personality Safety in Innovative Educational Environment - Lyudmila S. Podymova (National Research Mordova State University, 2018)
Introduction. This article considers a complex problem of personal safety in educational relations in course of implementation of pedagogical innovations. The personal safety demanded by science in this century as pedagogical phenomenon was designated to provide training of teaching staff in qualitatively other formats answering to realities of modern vital space. The innovative educational environment needs the optimum indicators of safety corresponding to objective conditions of development of the personality. The general characteristic of teaching staff readiness for personality safety in the innovative educational environment given on the basis of a complex of allocated indicators is especially relevant. The purpose of the article is to determine the readiness degree of teaching staff for personal security in the innovative educational environme nt. Materials and Methods. The complex of indicators of teaching staff readiness is estimated with the use of theoretical (idealization, abstraction, deductions, induction), and empirical (a pedagogical experiment, testing, selective direct observation, an experimental pedagogical conversation, questionnaire, professional and creative tasks, the statistical analysis of pedagogical information) methods. Materials and methods are demanded in the context of integration of the signs defining safety of the personality and significant parameters of innovation of the educational environment. Results. The general level of teaching staff readiness for personal safety in the innovative educational environment can’t be estimated as sufficient. The special attention is required to the work associated with formation of teaching staff readiness to take risk in the course of implementation of pedagogical innovations; also the low level of self-esteem and self-acceptance, sensitiv ity to themselves cause concern. This research expanded representations about personal safety in the innovative educational environment as to the system of the conditions providing openness of subjects of education to culture, innovations, situations of the uncertain future and also security and optimality of int eraction with the world around. Discussion and Conclusion. The target reference points of training teaching staff for evidence-based process of ensuring personality safety in the innovative educational environment are designated. The results of the study are of interest to scientific and pedagogical community, the practicing teachers, administrative employees of the educational organizations and future teachers.